Subjectivities promoted by food and nutrition policies: The case of Comuna 1 Popular in Medellín, Colombia - Paula Andrea Giraldo-López; Lorena Mancilla-López; Luz Adriana Muñoz-Duque (Salud Colectiva, 2025)
The aim of this study was to understand the subjectivities promoted by food and nutrition policies in Comuna 1 Popular of Medellín. Based on a qualitative design grounded in constructivist grounded theory, 20 semi-structured interviews were conducted between 2022 and 2023 with program users, social leaders, and those who implement food and nutrition programs in the comuna. Among the main findings, it was identified that public food and nutrition policies shape precarious subjectivities through mechanisms such as the homogenization of food and nutrition care for users. The administrative aspects of the programs limit the development of effective actions, and participation has low political impact. It is concluded that the vision and alienation of individualized subjects restrict the possibilities for collective action; however, social leaders promote actions aimed at mobilizing adjustments in the functioning of these policies and programs.